2015
DOI: 10.1055/s-0035-1566294
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor/Placental Growth Factor Heterodimer Levels in Preterm Infants with Bronchopulmonary Dysplasia

Abstract: Higher plasma VEGF/PlGF levels were found in preterm neonates with BPD and in those who died in the first 28 days of life, suggesting an important role of this substance in pulmonary vascular development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…Low levels circulating at birth may represent a primary defect in production by the dysfunctional placenta, upstream regulators, or competition with VEGF-A for the receptor antagonist sFlt-1. 32 Consistent with our findings, Procianoy et al 35 reported an increased ratio of VEGF/PIGF in postnatal blood samples (within 72 hours) from infants with BPD, suggesting that the relative VEGF-A to PIGF concentrations observed at the time of birth persist in the immediate postnatal period. Further studies are needed to assess how PIGF and VEGF-A levels vary over time, and whether the imbalance in angiogenic factors contributes to the development of BPD only, BPD with PH, or both.…”
Section: Discussionsupporting
confidence: 91%
“…Low levels circulating at birth may represent a primary defect in production by the dysfunctional placenta, upstream regulators, or competition with VEGF-A for the receptor antagonist sFlt-1. 32 Consistent with our findings, Procianoy et al 35 reported an increased ratio of VEGF/PIGF in postnatal blood samples (within 72 hours) from infants with BPD, suggesting that the relative VEGF-A to PIGF concentrations observed at the time of birth persist in the immediate postnatal period. Further studies are needed to assess how PIGF and VEGF-A levels vary over time, and whether the imbalance in angiogenic factors contributes to the development of BPD only, BPD with PH, or both.…”
Section: Discussionsupporting
confidence: 91%
“…For example, studies suggest disruption to placental development and hemodynamics, especially in the first month of pregnancy, could be reflected in fetal cardiac abnormalities and congenital heart disease (Linask, 2013; Linask et al, 2014; Burton and Jauniaux, 2018). Dysregulation of inflammatory and angiogenic factors (i.e., via maternal infection) during a critical period of lung development is associated with bronchopulmonary dysplasia and increased neonatal mortality in the first 28 days of life (Thébaud and Abman, 2007; McAdams et al, 2012; Procianoy et al, 2015). Furthermore, a large and rapidly growing body of evidence has linked maternal immune activation and dysregulation of angiogenesis with impaired fetal neurodevelopment and long-lasting neurocognitive and neuropsychiatric sequelae for offspring (Knuesel et al, 2014; Estes and McAllister, 2016; Brown and Meyer, 2018).…”
Section: Fetal Development Is Impacted By Dysregulation Of the Inflammentioning
confidence: 99%
“…Moreover, the evidence provided by Procianoy et al . has documented that the levels of Pgf were elevated in preterm neonates suffering from BPD (Procianoy et al, 2016 ), indicative of a potential association between Pgf and pathophysiological process of BPD. Pgf mRNA expression was found predominantly expressed by the vasculosyncytial membrane of villous trophoblast, and maternal decidual cells showed strong staining for Pgf immunoreactive protein (Khaliq et al, 1996 ); therefore, Pgf is essential for the angiogenesis of placental chorionic membrane, and also for the embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists suggesting that p65 could directly bind to the promoter region of placental growth factor (Pgf)/Plgf and transcriptionally activates the expression of Pgf/Plgf (Cramer et al 2005 ). Pgf is a member of the vascular endothelial growth factor (VEGF) family of angiogenesis regulators and the molecular structure is glycoprotein homodimer; higher plasma VEGF/Pgf levels have been found in preterm neonates with BPD and in those who died before 28 days of life, indicating an important role of this substance in pulmonary vascular development (Procianoy et al, 2016 ). Moreover, a previous animal model study has confirmed that Pgf overexpression impairs lung development in newborn rats, while its inhibition using an anti-PGF antibody ameliorates the lung impairment (Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%